Pembentukan Identitas Sosial dan Gerakan Keagamaan Kelompok Eks Preman Solo (Ekspreso) - Warsito Warsito (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2024)
This study discusses how to shape the religious identity of former thugs in the city of Solo who are gathered in the ex-thug Solo (Ekspreso) group and then mobilize them in da'wah and social movements. This study uses a qualitative method with a phenomenological approach. Data collection through interviews, observation and documentation. The data is analyzed using an interactive technique that takes and selects data until the data reaches saturation point and then describes it. This study found the formation of the religious identity of ex-thugs by internalizing religious and group values to members through routine weekly reviews. The management of the Ekspreso group is able to mobilize members in the da'wah and social movements. The da'wah movement includes the study of Aqidah and monotheism on Tuesdays and Fridays while coaching the reading of the Qur'an on Thursdays. Social movements in the form of coffee alms at Muslim events and the Movement to distribute rice to street people and unskilled workers in Solo. Apart from engaging in charity, Ekspreso also seeks to empower members' economies by providing business assistance and selling merchandise.